SEMANGAT KERJA KARYAWAN DITINJAU DARI KONSEP PENERIMAAN DIRI - Ernawati, Sri; Kholid, Abdul (Universitas Sahid Surakarta, 2012)
An employees as a valuable companyâs assets, ned to optimalization empowerment and largement. Employee morale is one of the causes, which self acceptance influenced. ThisÂ experiments aimed to understand the correlations of employee morale in terms of the concept of self acceptance. Fourty persons as a population have been analyzed with product moment correlations. The normaly assumption for self acceptance scale is rÂ² = 7,314 (p > 0,05), and for employee morale scale is rÂ² = 9,496 (p > 0,05). It showed both are in normal assumption. For the linierity, the F differences = 0,001 (p > 0,05) for both variables, it showed both are linier.The statistics analysis shows that rxy = 0,495 (p < 0,01), means that there is a significantly correlations of employee morale in tens of the concept of self acceptance. The conclusions is that self acceptance variables give 24,5% influnced to employee morale, and 75,5% given to other factors.